The Body Confident Mums challenge: a feasibility trial and qualitative evaluation of a body acceptance program delivered to mothers using Facebook - Krystina Wallis; Ivanka Prichard; Laura Hart; Zali Yager (BMC, 2021)
Abstract Background Motherhood is a time of intense physical, psychological, and identity transformation, and body dissatisfaction may emerge through the process of pregnancy, birth, and adaptation to parenting. We present a feasibility trial of the Body Confident Mums Challenge, a program developed by adapting existing, effective interventions that focus on self-compassion and appreciation of body functionality to be specific to mothers. Methods The program was delivered using the social learning function in a closed Facebook group. Qualitative evaluation of evidence of change was conducted by gathering individual written reflections posted during the challenge (n = 120). Feasibility and acceptability was determined using a feedback survey (n = 22). Results Participant's reflective posts indicated that they were embracing self-compassion, and de-prioritising body image concerns during the challenge. Feedback indicated that the program was mostly feasible and acceptable for mothers, with recommendations from some participants relating to slowing the pace of content delivery and reducing the time commitment of the Challenge. Conclusions The social media environment may therefore be a useful setting in which to implement brief intervention programs to improve body image and wellbeing.